Artificial Intelligence As An Innovation Mobile In Future Education - Armizi, Armizi; Fahrina Yustiasari Liriwati; Zulhimma, Zulhimma; Zulhammi, Zulhammi (International journal of technology and education research, 2023)
This abstract discusses the role of AI as a driver of innovation in future education. AI is capable of analyzing big data and providing deep insights into student learning patterns, preferences, and individual needs. By leveraging advanced data analysis technologies, AI can construct a unique learning profile for each student, creating a personalized learning experience. In addition, AI also contributes to the development of innovative curriculum and learning materials. With its ability to identify students' weaknesses and strengths in real time, AI can develop relevant curricula and learning materials that match students' levels of understanding and interest. This can increase the efficiency and effectiveness of learning in the classroom, thereby optimizing the potential of each student. AI-based virtual assistants are also a valuable support in the learning process. They can provide real-time help and feedback to students, guide them through learning challenges, and provide solutions to problems they face. Thus, virtual assistants play an important role in increasing student participation and engagement in learning. All in all, artificial intelligence has opened up new opportunities in the education of the future. With judicious application, AI can be a powerful partner for educators in enhancing learning and helping students reach their full potential. AI innovation in education will play a critical role in creating a more inclusive, adaptive and student-oriented future of education.